Prevalence and pattern of adult maxillofacial injuries: An institution-based retrospective study - Thanvir Mohamed Niazi; Asok Kumar Ramasamy Subramanian; Cathrine Diana; Natesh Pughalaendhi; Ulaganathan Gurunathan; Nithya Ganesh Sappaniapillai Kathiresan (Wolters Kluwer Medknow Publications, 2020)
Introduction: Maxillofacial injuries are more prevalent in road traffic accidents (RTAs). The incidence of RTAs tends to vary with geographical location, socioeconomic status, religion etc. Aim: The main aim of this study is to determine the pattern and prevalence of maxillofacial injuries reported to our institution. Materials and Methods: Data were obtained from medical records of the patients from January 2007 to December 2017 reported in CSI College of Dental Sciences and Research, Madurai, Tamil Nadu were retrieved and analyzed. Data include age, gender, etiology, site of injury, anatomical site associated injuries and their management were recorded and analyzed with STATA software version 14 (StataCorp LLC, College Station, TX, USA). Results: Maxillofacial injuries occur more commonly in 2nd and 3rd decade (40.44%) with mean age of 32.58 ± 11.15 years. RTA (77.21%) and alcohol influence (51%) were considered as the most common cause of maxillofacial injuries and was statistically significant. Mandible (44.85%) was most commonly involved and 62.5% required a surgical intervention. Conclusion: RTA with mandibular fracture is predominant in men between the age group of 20-30 years. Expansion in road network, increase in motorization, alcohol consumption and urbanization in developing countries had accompanied with rise in RTAs. Thus the use of safety devices and educating people by conducting preventive camps about traffic rules will reduce the number of RTA.